2004
DOI: 10.1242/jcs.00834
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of p53 target genes to p73 overexpression in SH-SY5Y neuroblastoma cell line

Abstract: p73, the first p53 gene homologue, encodes an array of p73 proteins including p73α full-length (TAp73α) and amino-truncated isoforms (ΔNp73α), two proteins with opposite biological functions. TAp73α can induce tumor suppressive properties, while ΔNp73α antagonizes p53 as well as TAp73 in a dominant-negative manner. In human malignant neuroblasts, p53 protein is wild-type but known to be excluded from the nucleus, therefore disabling its function as a tumor suppressor. The present study investigates whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 35 publications
9
29
1
1
Order By: Relevance
“…In the absence of cisplatin, p53 protein accumulation was induced by TAp73· as well as by ΔNp73· overexpression, as has been previously reported using the adenoviral system (14). This accumulation in untreated SH-SY5Y cells might be the result of stabilization induced by competition for MDM2 as p73 is known to form a stable complex with MDM2 (18,19).…”
Section: Tap73· and δNp73· Differentially Regulate P53/p73 Target Gensupporting
confidence: 77%
See 1 more Smart Citation
“…In the absence of cisplatin, p53 protein accumulation was induced by TAp73· as well as by ΔNp73· overexpression, as has been previously reported using the adenoviral system (14). This accumulation in untreated SH-SY5Y cells might be the result of stabilization induced by competition for MDM2 as p73 is known to form a stable complex with MDM2 (18,19).…”
Section: Tap73· and δNp73· Differentially Regulate P53/p73 Target Gensupporting
confidence: 77%
“…Importantly, ΔNp73 is known to play a role in various human tumors (11) whereas TAp73 may be involved in development and differentiation processes in normal cells, particularly in neurons (12). In previous studies, we reported that ΔNp73 is the only accumulated isoform in undifferentiated NB (13), and that TAp73· cooperates with wt-p53 to efficiently induce apoptosis (14).…”
Section: Introductionmentioning
confidence: 92%
“…In this study, we investigated the ability of nutlin-3 to induce apoptosis in a p53-null and doxorubicin-resistant NB cell line, LA155N. LA155N contains p73, a homologue of p53 which occurs in multiple isoforms and is required for some NB cell differentiation (9,10,12). It is known that the p73 gene has at least two promoters and the resulting protein products have distinct and opposing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Like UR61 cells, the human SH-SY5Y and NTera2 cells contain a wild-type p53 gene [22][23][24] To determine whether p73 activation of the MAPK cascade was independent of p53 status, we performed a similar experiment in SaOs-2, a p53 null human osteosarcoma cell line with no oncogenic Ras, 25 and in HCT116p53À/À cells. Ectopic expression of TAp73a and b induced Elk1 activity (Figure 5a and b) in both cell lines.…”
Section: Resultsmentioning
confidence: 99%